Pharmacological management of portal hypertension and its complications in children: lessons from adults and opportunities for the future. (11th February 2021) - Henkel, Sarah; Vetterly, Carol; Squires, Robert; McKiernan, Patrick; Squires, James
ABSTRACT: Introduction: Portal hypertension (PHT) and its complications in children are thought to be distinct from adult PHT in several areas, including the underlying bio-physiology of a child in which PHT develops, but also because of the pediatric-specific etiologies that drive disease progression. And yet pharmacologic approaches to PHT in children are mainly based on adult data, modified for pediatric practice. This reality has been driven by a lack of data specific to children. Areas Covered: The authors discuss current therapeutic approaches to PHT in children, including management of acute gastrointestinal variceal bleed, pharmacotherapy in prophylaxis, and established and emerging therapies to combat systemic co-morbidities that result from PHT. The few areas where pediatric-specific data exist are highlighted and the many gaps in knowledge that remain unresolved are underscored. Expert opinion: Despite decades of experience, optimal management of pediatric PHT remains undefined. In large part, this can be directly linked to a lack of basic understanding related to the unique pathophysiology and natural history that defines PHT in children. As a result, meaningful research into the utility and effectiveness of pharmacotherapy in children with PHT remains in its infancy. Large, multi-center, prospective studies will be needed to begin to establish an infrastructure on which a pediatric-specific research agenda can be built.